Time-dependent stomatal conductance and growth responses of Tabernaemontana divaricata to short-term elevated CO2 and water stress at higher than optimal growing temperature - Shaijal Babu Thruppoyil; Taoufik Ksiksi (Current Plant Biology, 2020)
A study was designed to evaluate the time-dependent short-term growth adjustments of Tabernaemontana divaricata plants to e[CO2] and WS treatment combinations (combinations) at higher than optimal growing temperature. Three CO2 treatments, i.e., 1000 ppm, 700 ppm (both e[CO2] and 435 ppm (ambient CO2 or a[CO2]) in combination with three WS treatments, i.e, control (CWS; irrigated to field capacity (FC)/4 days), moderate water stress (MWS; irrigated to 70% of FC/4 days) and high water stress (HWS; irrigated to 30% of field capacity/4 days) were randomly applied to plants. Data on stomatal conductance (gs), plant height (PH) and plant girth (PG) were analyzed for three time points (T1, T2 and T3) and for two 14-day periods (FFD and SFD) and one 28-day period (FTD) based on the time points. The 1000HWS (e[CO2] ×WS combination) increased gs at all time points and the 1000MWS increased gs, PH and PG at T3, compared to 435HWS and 435MWS, respectively. Dominant e[CO2] effects over WS effects during SFD period led to significant increase in gs, PH and PG for e[CO2]×WS compared to a[CO2]×WS treatment combinations. This effect during SFD time period, significantly contributed to the increase in gs, PH and PG during FTD, which included the effects of both FFD and SFD periods. Positive repeated measure correlations were observed for gs vs. PH, gs vs. PG and PG vs. PH comparisons. Overall, larger (taller and thicker) plants with higher gs were seen at T3 for e[CO2]×WS combinations compared to the a[CO2]×WS combinations. These results suggest that gs might not be a growth limiting factor for water-stressed T. divaricata plants growing in e[CO2] at higher than optimal growing temperature, provided the temperature stress is not extreme.